Pengaruh Beban Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan PT PLN (Persero) ULP Dinoyo - Basory, Hartomy Akbar; Asepta, Uki Yonda; Angelina, Monica (STKIP PGRI SITUBONDO, 2024)
PT Perusahaan Listrik Negara (Persero) is an electricity company with many employees responsible for providing services to the community. This scientific work will focus on the Dinoyo Customer Service Unit (ULP) to examine the effect of workload as variable X1 and job satisfaction as variable X2 on employee performance as variable Y PT PLN (Persero) ULP Dinoyo. PLN employees with effective workloads can help MSMEs by providing reliable electricity services and assisting MSMEs in adopting technology and innovation. PLN employees who are satisfied with their work can help MSMEs by providing better services and being more proactive in helping MSMEs. PLN employees with good performance can help MSMEs by increasing the efficiency and productivity of MSMEs and opening new market opportunities for MSMEs. This scientific work aims to research the impact of workload and job satisfaction felt by employees at PT PLN (Persero) ULP Dinoyo and its correlation with performance. The population in this study amounted to 80 people while the sample collected was 44 people. Data analysis techniques are performed using multiple linear regression. The results of the study simultaneously showed that variable workload and job satisfaction have a positive and significant influence on the performance of employees of PT PLN (Persero) ULP Dinoyo.